Optimization of biodiesel production from mixed ceiba pentandra and rice bran oil assisted by ultrasound - Kusumo F.; Shamsuddin A.H.; Ahmad A.R.; Silitonga A.S.; Fazril I. (Alpha Publishers, 2023)
The current research aims to examine the feasibility of production of biodiesel with non-edible mixed oils, Ceiba Pentandra Oil (CPO) and Rice Bran Oil (RBO).Several blends of CPO and RBO, ranging from 10:90 to 50:50% w/w were put under evaluation. The transesterification process variables of CP50RB50 as the suitable blend using exposure surface methodology, they were enhanced (RSM). The proportion of methanol to gasoline, the time of reaction and the concentration of the catalyst were both the key process parameters tested.An response surface transesterification process conditions such as KOH catalyst concentration are preferable: 0.83 percentage wt, methanol to oil ratio: 55.36%, reacted for 18.58 min18.58 min, with methyl ester yield of 98.7 %. The result indicates that the CP50RB50 methyl ester properties satisfy the biodiesel requirements as laid in standards, ASTM D6751 and EN 14214. 2020 Alpha Publishers.